A contribuição de mecanismos de governança de tecnologia da informação na gestão de terceirizações em uma instituição financeira - Menezes, Leonardo Silva de (2017)
The subject of Information Technology Governance (ITG) has attracted interest from both academia and organizations. This interest is due both to the relevance and impact of Information Technology (IT) for companies and society, as well as to how governance can justify and optimize IT investments. As part of these investments have been directed at IT outsourcing and organizations have faced a series of challenges in the management of these processes, the objective of this study was to propose a set of governance mechanisms, which are relevant for the management of IT outsourcing to organizations involved in outsourcing processes. For this study, ITG was considered a three mechanisms groups organized in structure, processes and relationship. In addition to the set of mechanisms, the archetypes for IT decision-making proposed by Weill and Ross were also considered. For GTI mechanisms, a list with 44 mechanisms identified in the work by Wiedenhoft and Klein in 2013 was used as the initial reference. The research adopted different techniques in data collection. In the first stage, a survey was conducted with 88 IT professionals related to the IT outsourcing process, including IT vendors who provide services to the organization where the study was carried out. In the second stage, 12 interviews were carried out with professionals directly involved in the pre-contract and post-contract of IT vendors. Finally, a focus group was carried out with the team responsible for IT Vendor Management of the organization that constitutes the case of this research. Based on a theoretical framework, the study started with an initial list of 44 mechanisms, which, after executing the three stages of the research, resulted in a list of 23 relevant mechanisms in the management of the IT outsourcing process. Of these 23 mechanisms, 10 mechanisms emerged throughout the research, consisting of a contribution to the evolution of the ITG, focused on outsourcing relationships. The final list of mechanisms was correlated with business and IT needs that guide this type of process, as well as problems arising from it, identified in the interviews stage, demonstrating the practical contribution of the applicability of such mechanisms, thus becoming relevant in the evolution of future studies, as well as the applicability of the mechanisms by organizations that carry out or will carry out the IT outsourcing.